Sex, Lies et les Franco-Manitobains de Marc Prescott : de l’esclandre étudiant (1993) au classique avant-gardiste (2013) - Louise Ladouceur (Continents manuscrits)
This paper analyses the case of a play written by Marc Prescott, a dramatist of Western Canada, fluent in English as in French. The play shows a specific language used in contemporean Manitoba (1993-2013), mixing English and French. Therefore the relationship between the two languages and the two communities in this western area of Canada is pictured. The study of the different re-writings of the play between the first performance in Saint-Boniface, Manitoba, in 1993, and the one given in Quebec in 2013 makes us understand the political, social and cultural backgrounds of « bilinguism », as it is assumed, or not, today. It shows also how different francophone areas of Canada consider their relationship with the two official languages of the country.